EFFICIENCY OF THYMOL AND CARVACROL IN ACTIVATION OF PATHOGENESIS RELATED GENES IN WHEAT AGAINST PUCCINIA STRIIFORMIS - E. I. El-Shafeey; A. A. Aboulila; E. H. Wheish; M. A. Ashmawy3and M. M. Elsharkawy1 (Journal of Animal and Plant Sciences, 2022)
Genetic resistance, which can be succeeded by combining several resistance genes, is the most helpful technique for controlling stripe rust disease (Puccinia striiformis). Nineteen wheat commercial cultivars were assessed for stripe rust resistance and the existence of four resistance genes were validated.Yr5 gene was found in all the studied genotypes in different sizes ranged from 467 bp to 581 bp, while Yr18 appeared only in four studied genotypes. The potential of thymol and carvacrol as bioactive compounds was investigated against stripe rust disease. Using real-time PCR, the regulation of defense genes expression was assessed. The findings of the present investigation indicated that both thymol and carvacrol had protective effects against stripe rust. Treatments with thymol and carvacrol boosted the incubation and latent periods of the disease. Additionally, in both treatments, the level of infection was lower than the control group. A significant up-regulation of the defense genes in wheat (PR5, PR6, PR8 and PR12) was recorded after treatment with thymol (100 mg/l) for 0, 1, 3, 4, 8 and 14 days after inoculation (DAI) and the fold change was close to the transcription of PR genes in the resistance monogenic line Yr15. After inoculation, carvacrol (100 mg/l) induced a significant up-regulation in the expression of PR genes at all days, except at 3 DAI (for PR6 and PR8) and 4 DAI (for PR6 and PR12). These results suggest that thymol and carvacrol may be utilized as elicitors of systemic resistance to stripe rust in wheat.
Keywords: Wheat; stripe rust; Yr Resistance genes; Thymol; Carvacrol; induced resistance; Pathogenesis related genes